Unveiling Angkasa Pura Airport's Economic Efficiency Through DEA Analysis - Azmieti Kurnia Sinta; Edi Abdurachman; Prasadja Ricardianto; Yuliantini Yuliantini (Dinasti Publisher, 2024)
This study aims to analyze the economic efficiency of airports in Angkasa Pura I, especially since the formation of the Tourism SOE holding in 2022 which changes airport operations. This study examines efficiency during the COVID-19 pandemic by introducing Air Traffic Movement (ATM), Air Passenger Movement (APM), and Air Cargo Movement (ACM) variables as output variables, which provide new insights that have not been explored before, especially the study in all Angkasa Pura I airports. This study uses quantitative research methods with non-parametric techniques to analyze efficiency and economies of scale in the aviation industry. The analytical tool used is Data Envelopment Analysis (DEA) using STATA 17 software as the main tool to evaluate efficiency and economies of scale at 16 airports. The results revealed variations in the level of efficiency of economies of scale among airports, with some airports improving their efficiency in response to the pandemic. The study confirms the importance of effective management strategies, transparency in information dissemination, and continuous monitoring in shaping airports' economic efficiency.